Flexibility Equipment of Protection, Control and Measure for Mean and Low Electrical Network in Power Transformation Substations - Bjelić, S.; Popović, G. (Elektronika ir Elektrotechnika, 2009)
A digital devices designed to achieve protective functions as control and measure function for low electrical network and devices is described in the paper. The equipment includes protection functions for isolated neutral networks or networks grounded via a resistor or via an arc suppression coil as well as control and measurement functions. The device takes advantage of digital signal processing and multiprocessor techniques to obtain improved performance. In addition to improved performance, the equipment also provides self-checking functions, a user friendly man-machine communication and serial interfaces for to SCADA systems. Ill. 10, bibl. 9 (in English; summaries in English, Russian and Lithuanian).